2019
DOI: 10.3390/app9194181
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Turbine Blade with an Under-Platform Damper Considering the Bladed Disc’s Rotation

Abstract: High-cycle fatigue (HCF) failure of the turbine blades of aero-engines caused by high vibrational stresses is one of the main causes of aero-engine incidents [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In Reference [19], the vibrations of turbine blades are considered, while removing one the assumptions often employed, i.e., the bladed disc's rotation. The work contributes to a better understanding of the dynamics contributions to be considered when designing under-platform dampers.…”
Section: Vibration Control and Dampingmentioning
confidence: 99%
“…In Reference [19], the vibrations of turbine blades are considered, while removing one the assumptions often employed, i.e., the bladed disc's rotation. The work contributes to a better understanding of the dynamics contributions to be considered when designing under-platform dampers.…”
Section: Vibration Control and Dampingmentioning
confidence: 99%
“…Yang et al [29] investigated the influence of the parametric uncertainties on the dynamic characteristics of a rotor-blade system. He et al [30,31] studied the influence of the convective inertial force and Coriolis inertial force on the vibration reduction of dry friction damped blades considering the rotation of the bladed disc.…”
Section: Introductionmentioning
confidence: 99%
“…Sayed et al [32] studied the effect of energy consumption and the viscous and slip transitions of an underplatform damper system, which showed that the contact state of optimal vibration reduction was half-stuck and half-slip. He et al [33] found that with the external excitation amplitude increasing, the vibration reduction of the transient response may be negative, and a larger normal load would be needed to maintain the vibration reduction efficiency of the damper. In [34], with uniform, linear and Hertzian normal load distributions, the dynamic characteristic of a one-dimensional friction system was discussed, which indicated that within a steady-state cycle, the energy dissipation of friction force of uniform distribution increases by 30% compared to that of linear distribution.…”
mentioning
confidence: 99%